The New Tapered Fiber Connector and the Test of Its Error Rate and Coupling Characteristics - Qinggui Hu; Chengzhong Li (International Journal of Optics)
Since the fiber core is very small, the communication fiber connector requires high precision. In this paper, the effect of lateral deviation on coupling efficiency of fiber connector is analyzed. Then, considering the fact that optical fiber is generally used in pairs, one for transmitting data and the other for receiving, the novel directional tapered communication optical fiber connector is designed. In the new connector, the structure of the fiber head is tapered according to the signal transmission direction. In order to study the performance of the new connector, several samples were made in the laboratory of corporation CDSEI and two testing experiments were done. The experiment results show that compared with the traditional connector, for the same lateral deviation, the coupling efficiency of the tapered connector is higher and the error rate is lower.